Soil-transmitted helminth infection, intestinal permeability, and intestinal inflammation in preschool-age children - Aulia, Gina; Djuardi, Yenny; Supali, Taniawati (Paediatrica Indonesiana, 2025)
Background Soil-transmitted helminth (STH) infection is a major health problem in low-and middle-income countries (LMIC). The presence and activity of STH can cause changes in the intestinal mucosa, including cell damage that can affect intestinal permeability and stimulate immune responses such as inflammation. Objective To assess the inflammatory and permeability status of the intestinal mucosa in various STH infections in preschool-age children residing in Nangapanda District, Ende Regency, East Nusa Tenggara. Methods In this cross-sectional study, stool samples were obtained from children aged 12-59 months and examined for worm eggs using the Kato Katz method. Concentrations of biomarkers for intestinal permeability and inflammation were measured by enzyme-linked immunosorbent assay (ELISA). We measured fecal alpha-1-antitrypsin (AAT) as an intestinal permeability biomarker and fecal calprotectin (FC) as an intestinal inflammation biomarker and evaluated the association between these biomarkers with STH infection. Results The prevalence of STH infection in 111 evaluated preschool-age children was 17.1%. Ascaris lumbricoides was the predominant species, followed by Trichuris trichiura. Most subjects (64.7%) had AAT levels >0.27 mg/g, while only 35.1% had FC >50 mg/kg. STH infection status was not significantly associated with AAT concentration status, even when analyzed by STH species. A significant association was found only between T. trichiura infection and FC concentration. In this study, which included infected and uninfected groups, children infected with T. trichiura had higher concentrations of FC than those uninfected. Conclusion STH infection was not significantly correlated with fecal biomarkers except between T. trichiura infection status and increased gut inflammatory biomarker. AAT levels were generally elevated in the evaluated preschool-aged population regardless of STH infection, indicating that other factors may have contributed to increased gut permeability.